Methods of communication and mediating processes in realistic job previews. - Colarelli, Stephen M. (Journal of Applied Psychology, 1984)
A field experiment was conducted to investigate the effectiveness of two methods of presenting realistic job previews (RJPs) to applicants and to examine possible mediating processes involved in RJPs The study was conducted in a large metropolitan bank, using a sample of 164 bank tellers Teller applicants who were offered jobs were assigned to one of three groups (a) a treatment group in which job applicants received a realistic job preview from an incumbent teller, (b) a treatment group in which applicants received a RJP brochure, and (c) a control group. Substantially fewer individuals in the incumbent condition left the job after 2 and 3 months than individuals m the brochure or control groups There was no significant difference in turnover between the brochure and control groups There was no support for self-selection and commitment to choice as mediating processes, the results regarding met expectations and stress as mediators were equivocal The evidence from several reviews of the literature indicates that realistic job previews (RJPs) tend to reduce turnover and have a positive effect on job attitudes (Reilly, Brown, Blood, & Malatesta, 1981; Wanous, 1977, 1980). These effects, however, tend to be small. Such results have prompted some authors to suggest that little should in fact be expected from RJPs (Lewis, 1980; Reilly et al., 1981; Schwab, 1981; Tenopyr & Oeltjen, 1982). This conclusion may be premature, given that little is known about the effectiveness of different methods of providing applicants with realistic information or about why RJPs may be beneficial The purposes of this research were to examine (a) the effectiveness